2022
DOI: 10.1021/acsomega.2c04101
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Performance Analysis of Form-Stable Composite Phase Change Materials with Different EG Particle Sizes and Mass Fractions for Thermal Energy Storage

Abstract: The low thermal conductivity and leakage of paraffin (PA) limit its wide application in thermal energy storage. In this study, a series of form-stable composite phase change materials (CPCMs) composed of PA, olefin block copolymer (OBC), and expanded graphite (EG) with different particle sizes (50 mesh, 100 mesh, and 200 mesh) and mass fractions are prepared by melt blending. OBC as a support material could reduce PA leakage during melting, and EG as a thermally conductive filler can improve the thermal perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…This is because the movement of CA-PA molecules is limited due to the pore size of EVM, and the crystallization behavior of CA-PA is obviously oriented towards (005) crystal plane. [46][47][48] XRD analysis showed that no chemical reaction occurred between CA-PA eutectic and EVM. Moreover, the characteristic diffraction peaks of CA-PA/ EVM-1 and CA-PA/EVM are nearly unchanged aer 100 phase change cycles.…”
Section: Crystalloid Phase Of Composite Pcmsmentioning
confidence: 99%
“…This is because the movement of CA-PA molecules is limited due to the pore size of EVM, and the crystallization behavior of CA-PA is obviously oriented towards (005) crystal plane. [46][47][48] XRD analysis showed that no chemical reaction occurred between CA-PA eutectic and EVM. Moreover, the characteristic diffraction peaks of CA-PA/ EVM-1 and CA-PA/EVM are nearly unchanged aer 100 phase change cycles.…”
Section: Crystalloid Phase Of Composite Pcmsmentioning
confidence: 99%